2018
DOI: 10.21273/hortsci13484-18
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Substrate Moisture Content during Greenhouse Production of Poinsettia Improves Postproduction Quality and Economic Value

Abstract: The objective was to determine the effect of substrate moisture content (SMC) during poinsettia (Euphorbia pulcherrima) greenhouse production on plant quality, postproduction longevity, and economic value. Two experiments were conducted, one in 2016 with ‘Freedom Red’ and the other in 2017 with ‘Christmas Eve Red’. Treatments included two SMC levels (20% or 40%) applied in four timing of application combinations. Total production (TP) time was 14 (2016) or 12 (2017) weeks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…There are opportunities for additional research to evaluate whether the responses we discovered are consistent across other growing media and how PGR, which were not used in our trial but are commonly sprayed on poinsettias, affect transpiration. Although our study differs in many aspects (e.g., experimental design and physiological measures) from the Guo et al (2018) research, our results provide complementary evidence supporting the idea of decreasing poinsettia irrigation scheduling by 50% from 0.4 to 0.2 m 3 • m -3 VWC. This is not the first time research could influence radical changes to poinsettia production.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…There are opportunities for additional research to evaluate whether the responses we discovered are consistent across other growing media and how PGR, which were not used in our trial but are commonly sprayed on poinsettias, affect transpiration. Although our study differs in many aspects (e.g., experimental design and physiological measures) from the Guo et al (2018) research, our results provide complementary evidence supporting the idea of decreasing poinsettia irrigation scheduling by 50% from 0.4 to 0.2 m 3 • m -3 VWC. This is not the first time research could influence radical changes to poinsettia production.…”
Section: Discussionsupporting
confidence: 66%
“…Our results indicate that poinsettia irrigation schedules that attempt to maintain 0.4 m 3 • m -3 VWC are applying excessive volumes of water, resulting in wasted resources and potential sources of pollution. It has been suggested that a standard commercial production irrigation schedule allows the substrate to dry down to 0.4 m 3 • m -3 VWC before rewatering to container capacity (Guo et al, 2018). Our results suggest that it was not until <0.2 m 3 • m -3 VWC that most of the weekly treatment plants began expressing water stress symptoms.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations